Penentuan Model Terbaik untuk Peramalan Data Saham Closing PT. CIMB Niaga Indonesia Menggunakan Metode Arch-Garch - Gatri Eka; Vebriani Safitry; Yesika Kristin (Jurnal Statistika dan Aplikasinya, 2017)
This study explains about forecasting model stock closing price data PT. CIMB Niaga Indonesia on June 2017. The goal of this research is to formulated forecasting model stock data of PT. CIMB Niaga Indonesia specially is that stock closing price data by using ARCH/GARCH model. The result that got is that ARCH(1) model is the suitable model to forecasting stock closing price data. Result of forecasting for daily later so that stock data specially stock closing price is being increase.